Produção de mudas de espécies florestais de restinga, com base em estudos florísticos e fitossociológicos, visando a recuperação de áreas degradadas, em Ilha Comprida - SP - Carrasco, Pablo Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
The sandbank forests, expression used in this work to designate the forest formations that grow on the coastal sandy plain, possess internal structural heterogeneity and are constituted by vegetation mosaics, being threatened by the building speculation, selective retreat of biological resources and mining activities. The production of native regional forest seedlings, with base on floristic and phytosociological studies, seeking the recovery of degraded areas, in Ilha Comprida - São Paulo State - Brasil, was the aim of this paper. They where studied four areas of 1ha each, by using the method of contiguous portions, becoming evident the presence of 106 native forest species (of wide geographical distribution) and 6 exotic species, being the family Myrtaceae the most representative. There were 23 common species to the four areas. The sampling sufficiency was reached in an area of 70m X 70m for those forest formations. Were registered the phytosociological parameters of 256 individuals for area, by applying the method of the point centered quarter, as well as collected soil samples, being submitted to the physical and chemical analyses. The four disturbed forest formations presented small structural complexity and low specific diversity, with small number of species being represented by many individuals. The soils were poor in nutrients and organic matter, with low fertility and high tenors of aluminum. The forest formations are similar to the ones of Cardoso's Island (São Paulo) and of Mel Island (Paraná - Brasil). In an area degraded by mining of sand, the planting of seedlings occurred directly in the sandy soil and in holes with addition of 50% of peat. During the 175 days of evaluation, the growth gains in height was not significant, being observed the mortality of 23.8% of the seedlings implanted in the soil with peat and 50.4% of the one of the sandy soil. The peat addition, although insufficient in nutrients, increased...

As florestas de restinga, expressão utilizada neste trabalho para designar as formações florestais que se desenvolvem sobre a planície arenosa litorânea, possuem heterogeneidade estrutural interna e são constituídas por mosaicos vegetacionais, sendo ameaçadas pela especulação imobiliária, retirada seletiva de recursos biológicos e atividades minerárias. A produção de mudas florestais nativas regionais, com base em estudos florísticos e fitossociológicos, visando a recuperação de áreas degradadas, em Ilha Comprida (SP), foi o objetivo deste trabalho. Foram estudadas quatro áreas de 1ha, pelo método de parcelas contíguas, evidenciando a presença de 106 espécies florestais nativas (de ampla distribuição geográfica) e 6 exóticas, sendo a família Myrtaceae a mais representativa. Houve 23 espécies comuns às quatro áreas. A suficiência amostral foi alcançada em uma área de 70 X 70m para essas formações florestais. Foram anotados os parâmetros fitossociológicos de 256 indivíduos por área, pelo método do quadrante centrado no ponto, bem como coletadas amostras de solo e submetidas às análises física e química. As quatro formações florestais perturbadas apresentaram pequena complexidade estrutural e diversidade específica baixa, com pequeno número de espécies representadas por muitos indivíduos. Os solos se mostraram pobres em nutrientes e matéria orgânica, com baixa fertilidade e teores elevados de alumínio. As formações florestais são similares às das Ilhas do Cardoso (SP) e do Mel (PR). Numa área degradada por mineração de areia, o plantio de mudas ocorreu diretamente no solo arenoso e em covas com 50% de turfa. Durante os 175 dias de avaliação, o ganho de crescimento em altura não foi significativo, sendo observada a mortalidade de 23,8% das mudas implantadas no solo com turfa e 50,4% das do solo arenoso. A adição de turfa, embora insuficiente em nutrientes, aumentou a taxa de...
Keywords: Ecologia vegetal; Florestas; Fitogeografia; Plant ecology